Combined genomics and proteomics unveils elusive variants and vast aetiologic heterogeneity in dystonia - Zech, Michael; Dzinovic, Ivana; Skorvanek, Matej; Harrer, Philip; Necpal, Jan; Kopajtich, Robert; Kittke, Volker; Tilch, Erik; Zhao, Chen; Tsoma, Eugenia; Sorrentino, Ugo; Indelicato, Elisabetta; et al. (Brain, 2025)
Dystonia is a rare disease trait for which large-scale genomic investigations are still underrepresented. Genetic heterogeneity among patients with unexplained dystonia warrants interrogation of entire genome sequences, but this has not yet been systematically evaluated. To significantly enhance our understanding of the genetic contribution to dystonia, we (re)analysed 2874 whole-exome sequencing (WES), 564 whole-genome sequencing (WGS), as well as 80 fibroblast-derived proteomics datasets, representing the output of high-throughput analyses in 1990 patients and 973 unaffected relatives from 1877 families. Recruitment and precision-phenotyping procedures were driven by long-term collaborations of international experts with access to overlooked populations. By exploring WES data, we found that continuous scaling of sample sizes resulted in steady gains in the number of associated disease genes without plateauing. On average, every second diagnosis involved a gene not previously implicated in our cohort. Second-line WGS focused on a subcohort of undiagnosed individuals with high likelihood of having monogenic forms of dystonia, comprising large proportions of patients with early onset (81.3%), generalized symptom distribution (50.8%) and/or coexisting features (68.9%). We undertook extensive searches for variants in nuclear and mitochondrial genomes to uncover 38 (ultra)rare diagnostic-grade findings in 37 of 305 index patients (12.1%), many of which had remained undetected due to methodological inferiority of WES or pipeline limitations. WGS-identified elusive variations included alterations in exons poorly covered by WES, RNA-gene variants, mitochondrial-DNA mutations, small copy-number variants, complex rearranged genome structure and short tandem repeats. For improved variant interpretation in WGS-inconclusive cases, we employed systematic integration of quantitative proteomics. This aided in verifying diagnoses related to technically challenging variants and in upgrading a variant of uncertain significance (3 of 70 WGS-inconclusive index patients, 4.3%). Further, unsupervised proteomic outlier analysis supplemented with transcriptome sequencing revealed pathological gene underexpression induced by transcript disruptions in three more index patients with underlying (deep) intronic variants (3/70, 4.3%), highlighting the potential for targeted antisense-oligonucleotide therapy development. Finally, trio-WGS prioritized a de novo missense change in the candidate PRMT1, encoding a histone methyltransferase. Data-sharing strategies supported the discovery of three distinct PRMT1 de novo variants in four phenotypically similar patients, associated with loss-of-function effects in in vitro assays. This work underscores the importance of continually expanding sequencing cohorts to characterize the extensive spectrum of gene aberrations in dystonia. We show that a pool of unresolved cases is amenable to WGS and complementary multi-omic studies, directing advanced aetiopathological concepts and future diagnostic-practice workflows for dystonia.
Keywords: dystonie; Humans; lidé středního věku; proteomics; Proteomics; Dystonia; genetická heterogenita; genomics; Female; whole-genome sequencing; genomika; dospělí; Whole Genome Sequencing; Dystonic Disorders; lidé; dystonické poruchy; sekvenování exomu; proteomika; sekvenování celého genomu; Adult; Genetic Heterogeneity; ženské pohlaví; Male; Middle Aged; dystonia; transcriptomics; mužské pohlaví; Genomics; Exome Sequencing; multi-omics